Employment projections for business students - Suarez Carvajalino, Luz Dary; Quintero Quintero , Wilder (Universidad Francisco de Paula Santander, 2017)
Employment prospects must be generated from the academic scenarios of the University. The purpose of the present article is to know the employment projections of the students of the ninth semester of Business Administration at UFPSO. The methodology of the investigation was quantitative with a descriptive scope by applying the survey under the questionnaire instrument. From the results, it is concluded that more than 40% of the students expect to enter the commercial sector, also, to get a job in less or equal to one year after graduation and, finally, the student has the vision to learn how to direct and lead processes, develop their skills and talents in order to obtain a good salary and recognition for their work.